Effect of the invader Boccardia proboscidea (Polychaeta: Spionidae) on richness, diversity and structure of SW Atlantic epilithic intertidal community. Issue 2 (28th February 2015) - Elías, Rodolfo; Jaubet, María L.; Llanos, Elizabeth N.; Sanchez, María A.; Rivero, María S.; Garaffo, Griselda V.; Sandrini-Neto, Leonardo
Highlights: An invasive polychaete outcompete bivalve ecosystem engineer. Boccardia proboscidea reef form monocultures, becomes an auto-ecosystem engineer. The structure of intertidal epilithic community change after polychaete invasion. Unique phenomenon in sewage-impacted areas of the SW Atlantic shore. Abstract: In Mar del Plata (Argentine, SW Atlantic), a large seaside resort, the sewage discharges impact the littoral ecosystem. The invader polychaete Boccardia proboscidea has developed reefs since spring of 2008. The effect of this species on the richness, diversity and structure of epilithic intertidal community was assessed through an MBACI design in both sewage-impacted and reference sites, and Before/After the invasion. The presence of reefs of B. proboscidea since spring 2008 has caused a significant reduction of total individuals, total taxa and diversity in sewage-impacted sites regarding the reference ones. The species analyzed showed a high variable response because patterns were dominated by small-scale variability. Occasional peaks in abundance were observed on a single sampling site and time and a large variation among replicates. The associated fauna, formerly rich and diverse in impacted sites, shows a tendency to disappear as the ecosystem engineer Brachidontes rodriguezii is replaced by monocultures of B. proboscidea.